Unveiling the Wave: Unraveling Sales Trends and Unlocking Market Basket Insights - Teh, Ming Ann; Lim, Tong Ming; Chin, Wan Yoke (International Journal of Membrane Science and Technology, 2023)
This article presents sales trends and market basket analysis for Food and Beverages (F&B) items recommendation using linear regression time series and association rules. The purpose of this study is to help businesses to make better informed decisions by understanding their customers’ purchasing behaviors and the sales trends of the F&B items. This includes the study of both cross- selling and up-selling patterns using market basket analysis. To improve the market basket analysis, food name clustering has been carried out to group those foods having similarity ratio higher or equal to 80 based on the Levenshtein distances between the food names. This study analyzes sales data from a mobile app platform that register the Malaysian F&B hawkers (or merchants) and app users (or buyers) who sell and purchase F&B respectively. This study is based on sales trends analysis and association rules of product recommendations by examining FP-Growth and the relationship between product items bought. This study provides valuable insights for local Malaysian hawkers who are looking to improve their F&B items recommendations and to make better data-driven decisions while planning their marketing activities. It helps to improve sales by either up or cross-sell their products more effectively.